SARS-CoV-2’s Variants of Concern: A Brief Characterization - Scovino, Aline Miranda; Dahab, Elizabeth Chen; Vieira, Gustavo Fioravanti; Freire-de-Lima, Leonardo; Freire-de-Lima, Celio Geraldo; Morrot, Alexandre (Frontiers in Immunology, 2022)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disclose the variants of concern (VOC) including Alpha (B.1.1.7), Beta (B.1.351), Gamma (P1), Delta (B.1.617.2), and Omicron (B.1.1.529). The spike protein (S) present on the surface of the virus is recognized by the host cell receptor, the angiotensin-2 converting enzyme (ACE2) in host cells which promotes their entry into the cell. The mutations presented by VOCs are found in RBD and the N-terminal region of S protein. Therefore, mutations occurring in RBD can modify the biological and immunogenic characteristics of the virus, such as modifying the spike affinity for ACE2, increasing the virus transmissibility, or conferring the ability to escape the immune responses. The raise of a potential new SARS-CoV-2 variant capable of evading the host defenses and at the same time maintaining its fitness justifies the importance of continued genetic monitoring of the pandemic coronavirus.